(untitled) (Journal of Entrepreneurship and Business, 2021)
Trilemma policy is a concept of international economics in which it is impossible to gain all three variables at once or also known as Mundell-Fleming framework. Trilemma policies consist of independent monetary policy, exchange rate stability, and free capital mobility. By pursuing any two of the variables, it will shadow the other one. On the other hand, sterilisation is the policy which is set by the central bank to limit the effect of inflow and outflow of the capital money supply. Trilemma policy affected the sterilisation, which is the proxy by central bank reserve due to the latter that depends on the former. The purpose of this study is to find the relationship between trilemma policy and sterilisation. The sample of the study focused on four countries such as Qatar, Kuwait, Indonesia, and Japan by collecting monthly data from the year 2009 to 2017. At the end of this study, the findings will verify whether it is possible to maintain all the three variables in trilemma policy to achieve a stable economic condition by sterilisation.